1997
DOI: 10.1002/hep.510260633
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence variations in the internal ribosome entry site of hepatitis C virus-1b: No association with efficacy of interferon therapy or serum HCV-RNA levels

Abstract: The extreme 5'-proximal sequences of the hepatitis C virus (HCV) genome including the 5'untranslated region (5'UTR) and the first 30 nucleotides of the core region are highly conserved, and serve as an internal ribosome entry site (IRES) that initiates the cap-independent translation of HCV polyprotein. Mutations in the IRES sequence have been shown to cause changes in the efficiency of protein translation in vitro. However, the significance of genetic variations in the IRES is not fully known in clinical sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 23 publications
(5 reference statements)
3
20
1
Order By: Relevance
“…In spite of that, no significant difference in viral load (reflecting enhance of translational activity) was related to these nucleotidic sites in this study. These results agreed with what it was mentioned previously (Yamamoto et al, 1997): sequence variability of HCV-IRES was not appearing to correlate with any difference in HCV-RNA concentration in the PBMCs which reflects the level of HCV replication. Obviously, viral population has established an equilibrium between the quasispecies and immune constraints.…”
Section: Discussionsupporting
confidence: 92%
“…In spite of that, no significant difference in viral load (reflecting enhance of translational activity) was related to these nucleotidic sites in this study. These results agreed with what it was mentioned previously (Yamamoto et al, 1997): sequence variability of HCV-IRES was not appearing to correlate with any difference in HCV-RNA concentration in the PBMCs which reflects the level of HCV replication. Obviously, viral population has established an equilibrium between the quasispecies and immune constraints.…”
Section: Discussionsupporting
confidence: 92%
“…To date, although little work has been undertaken in that direction, the HCV 5ЈUTR appears to be an element of choice for such an approach. Contradictory conclusions have been proposed concerning a possible correlation between the sequence variability found for HCV IRESs of different genotypes and a response to interferon therapy (15,22,32). Currently, work is under way to study HCV 5Ј UTR diversity displayed in a viral quasispecies population and its dynamics toward the viral life cycle under different biological pressures.…”
Section: In Vitro Translational Efficiency Of 5 Utr Quasispeciesmentioning
confidence: 99%
“…Several foot-printing, toeprinting and UV cross linking assays have shown that domain Ⅲ is the most active part in RNA-protein binding where it folds to form stem-loop structures for high affinity binding to host proteins [11,[17][18][19] . Although genomic variability in HCV IRES was shown as one mechanism for escaping IFNα effects, there has been www.wjgnet.com controversy with regard to the predictive value of pretreatment IRES genomic variations in determining later response to IFNα [20] . Although domain Ⅲ harbors only 22% of the overall IRES mutations in a mixed genotype population [21] , IRES activity seems to depend more on the location of mutant nucleotides which play the most important roles in IRES activity.…”
Section: Discussionmentioning
confidence: 99%